Being human in the digital world : interdisciplinary perspectives / edited by Beate Roessler, University of Amsterdam, Valerie Steeves, University of Ottawa. - össler, Beate; Steeves, Valerie M., 1959- (Cambridge University Press, 2025)
Being Human in the Digital World is a collection of essays by prominent scholars from various disciplines exploring the impact of digitization on culture, politics, health, work, and relationships. The volume raises important questions about the future of human existence in a world where machine readability and algorithmic prediction are increasingly prevalent and offers new conceptual frameworks and vocabularies to help readers understand and challenge emerging paradigms of what it means to be human. Being Human in the Digital World is an invaluable resource for readers interested in the cultural, economic, political, philosophical, and social conditions that are necessary for a good digital life. This title is also available as Open Access on Cambridge Core.